2017
DOI: 10.1111/cen3.12347
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, diagnosis and therapeutic strategies in pediatric multiple sclerosis

Abstract: Multiple sclerosis (MS) is a complex immune-mediated disease characterized by recurrent demyelinating episodes of the central nervous system, which typically occurs in young adults. It is the most common disabling neurological disease of young people; however, pediatric MS, defined as onset of MS before the age of 18 years, has been increasingly recognized worldwide in the past two decades. Pediatric MS might represent up to 10% of all patients with MS. As in adults, the diagnosis of pediatric MS rests on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…Certain studies have also registered the PP course in pediatric and adolescent patient population in about 3% of the cases [ 17 ]. A positive family history of MS existed in 9.3% of patients, while other studies reported results ranging from 6 to 8% [ 26 ], or most extremely from 2 to 19% [ 16 , 27 ]. In our PedMS group, 24.1% of patients had positive family history for other autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain studies have also registered the PP course in pediatric and adolescent patient population in about 3% of the cases [ 17 ]. A positive family history of MS existed in 9.3% of patients, while other studies reported results ranging from 6 to 8% [ 26 ], or most extremely from 2 to 19% [ 16 , 27 ]. In our PedMS group, 24.1% of patients had positive family history for other autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Monofocal onset of the disease in our study is consistent with other studies, which reported monofocal onset in 54% to 90% patients, usually after puberty [ 5 , 29 ]. However, a number of studies have reported multifocal onset of disease in 50 to 70% of the cases, and mostly before puberty [ 26 ]. The most common initial symptoms are similar to other studies [ 21 , 30 , 31 ], which also reported sensory deficits followed by loss of vision, motor deficit, lesions of the cerebellum and brainstem [ 5 , 9 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bersesuaian dengan yang ditemukan pada populasi dewasa, diagnosis MS pada populasi anak bertumpu pada ditemukannya lesi yang mengalami perluasan dalam ruang dan waktu (disseminated in time DIT and disseminated in space, DIS), serta juga bertumpu pada keberhasilan eksklusi sejumlah kondisi klinis lainnya yang menyerupai multipel sklerosis. 14 Pada laporan kasus ini, penulis menampilkan sebuah laporan kasus multipel sklerosis pada seorang anak perempuan berusia 13 tahun 7 bulan yang dirawat di bangsal anak RSUP Dr.M.Djamil Padang. Diagnosis multipel sklerosis pada pasien ini ditegakkan berdasarkan pada sejumlah penemuan manifestasi klinis yang ditunjang oleh pemeriksaan…”
Section: Pembahasanunclassified
“…Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system [1]. The term childhood MS is used in patients whose first clinical signs occur before 18 years of age [2]. The incidence of MS in children is rare, compared to MS in adulthood.…”
Section: Introductionmentioning
confidence: 99%